Métodos de diagnóstico de salmonella en huevos de gallinas comerciales - Diaz Burgos, Nezzar Alejandro (2023)
The present work to be carried out is based on the diagnostic methods of Salmonella in commercial chicken eggs, currently several scientists have expressed that this bacterial disease is one of the most serious problems that affect public health with the highest incidence and which leads to an increase in economic losses. For this reason, it is desired to demonstrate and determine the benefits of the tests to carry out a correct diagnosis in Salmonella and thus avoid the problems that are generated annually throughout the world. According to several authors, they have stated that there are various methods for the detection of this bacterial disease and these methods are isolation, which will express the result by presenting the absence or presence of the bacterium. In addition, there is that of selective and differential cultures that is based on the selection of certain microorganisms in order to prevent their development. In the penultimate one is the biochemical confirmation, this consists of the identification of the metabolic characteristics of the bacterium and obtaining its result in seconds. Finally, we find the serological tests or commonly known as (PCR) that are characterized by being a method based on the amplification and detection of DNA in vitro that determines the number of genes synthesized in the time of each reaction, its result will be appreciated. to obtain in a period of 24 to 36 hours. Finally, it is recommended that commercial chicken eggs be kept at temperatures of 12 °C to prevent Salmonella contamination